Estimation of inelastic seismic deformations in asymmetric multistorey RC buildings. - Kosmopoulos, A. J.
Four real buildings with three to six stories, strong irregularities in plan and little engineered earthquake resistance are subjected to inelastic response-history analyses under 56 bidirectional EC8-spectra-compatible motions. The average chord rotation demand at each member end over the 56 response-history analyses is compared to the chord rotation from elastic static analysis with inverted triangular lateral forces or modal response spectrum analysis. The storey-average inelastic-to-elastic-chord-rotation-ratio was found fairly constant in all stories, except when static elastic analysis is applied to buildings with large higher mode effects. Except for such buildings, static elastic analysis gives more uniform ratios of inelastic chord rotations to elastic ones within and among stories than modal response spectrum analysis, but generally lower than 1.0. With increasing EPA the building-average inelastic-to-elastic-chord-rotation-ratio decreases but scatter in the results increases. Static elastic analysis tends to overestimate the inelastic torsional effects at the flexible or central part of the torsionally flexible buildings and underestimate them at their stiff side. Modal response spectrum analysis tends to overestimate the inelastic torsional effects at the stiff or central part of the torsionally stiff buildings and underestimate them at the flexible side. Overall, for multistorey RC buildings that typically have fundamental periods in the velocity-sensitive part of the spectrum, elastic modal response spectrum analysis with 5% damping gives on average unbiased and fairly accurate estimates of member inelastic chord rotations. If higher modes are not significant, elastic static analysis in general overestimates inelastic chord rotations of such buildings, even when torsional effects are present.
Keywords: Asymmetric buildings; Inelastic seismic response; Irregular buildings; Multistorey buildings; Seismic displacements; Torsional seismic response